2017
DOI: 10.1136/postgradmedj-2016-134626
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal and multicentre study of burnout and error in Irish junior doctors

Abstract: Current levels of burnout are unsustainable and place the health of both junior doctors and their patients at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 24 publications
1
20
0
1
Order By: Relevance
“…In the interviews, these factors were also identified as common contributors (in the YCFF they are classified as 'individual staff' and were identified in 57% of the interviews). In a previous study it was found that around 70% of Irish junior doctors were burned out, 6 and in another study with the same population approximately half of the respondents were determined to be experiencing psychological distress. 5 Although a diary study of Irish interns appeared to indicate that interns were obtaining sufficient hours of sleep, it was common for them to work longer than their shift, with the medical intern on nightshift reporting particularly high levels of workload.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In the interviews, these factors were also identified as common contributors (in the YCFF they are classified as 'individual staff' and were identified in 57% of the interviews). In a previous study it was found that around 70% of Irish junior doctors were burned out, 6 and in another study with the same population approximately half of the respondents were determined to be experiencing psychological distress. 5 Although a diary study of Irish interns appeared to indicate that interns were obtaining sufficient hours of sleep, it was common for them to work longer than their shift, with the medical intern on nightshift reporting particularly high levels of workload.…”
Section: Discussionmentioning
confidence: 93%
“…The medical error survey was an adjunct survey completed as part of a larger study of burnout and error among Irish interns. 6 The medical error survey was only completed by those interns who reported making an error that 'played on your mind in the last 3 months'.…”
Section: Survey Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiences of junior doctors vary greatly depending on the settings within which they are placed [7,8]. The quality of training and supervision trainees receive during their first year of practice varies between medical teams and hospitals, and likely contributes to the high level of stress and burnout in junior doctors in the Republic of Ireland [9,10], and internationally [11,12]. It is also important to acknowledge that junior doctors do not all necessarily acquire the requisite skills to care for patients at the same pace [13].…”
Section: Introductionmentioning
confidence: 99%
“…Stress, burnout and impairment are substantial mental problems of doctors that have attracted increasing attention in recent years [2,3] . Burnout is an important factor affecting the QOL of young doctors and college students [4,5] . Anxiety, depression and other mental problems are also commonly reported in doctors [6] .…”
Section: Introductionmentioning
confidence: 99%